Comparative Study of Store Image, Patronage Intention, and Retail Mix Elements between Alfamart and Indomaret in Jakarta - Brian Garda Muchardie; Ferdian Yosa; Annetta Gunawan (Bina Nusantara University, 2017)
This research is initiated by the phenomenon of competitive rivalry between the two giant convenience stores (Alfamart and Indomaret) in Indonesia. Alfamart must strive to improve the patronage intention of its customers so that they do not switch to its main competitor, Indomaret. The purpose of the research was to compare patronage intention and store image between Alfamart and Indomaret. Additionally, this research clarified the influence of the components in the retail mix, which were in-store promotion, store atmosphere, convenience, and merchandise between Alfamart and Indomaret in the formation of store image and its impact on patronage intention. The research methods were independent t-test and path analysis. Independent t-test aimed to find differences that occurred between Alfamart and Indomaret especially the differences in the components of the retail mix, store image, and patronage intention. Meanwhile, path analysis was to determine the effect of the retailmix to store image and patronage intention. After processing the data, it is shown that both variables which are the components of the retail mix, store image, and patronage intention are surpassed by Alfamart. In Alfamart, thereare significant influences of in-store promotion, convenience, and merchandise to the store image and patronage intention. Similarly, in-store promotion, merchandise, and store image have direct influence on patronage intention.Meanwhile, for Indomaret, there is the influence of the in-store promotion, convenience, and merchandise to store image and patronage intention with conditions that store atmosphere and store image have a direct influence onthe patronage intention.